2002
DOI: 10.1128/jb.184.10.2709-2718.2002
|View full text |Cite
|
Sign up to set email alerts
|

Caulobacter crescentus Synthesizes an S-Layer-Editing Metalloprotease Possessing a Domain Sharing Sequence Similarity with Its Paracrystalline S-Layer Protein

Abstract: Strains of Caulobacter crescentus elaborate an S-layer, a two-dimensional protein latticework which covers the cell surface. The S-layer protein (RsaA) is secreted by a type I mechanism (relying on a C-terminal signal) and is unusual among type I secreted proteins because high levels of protein are produced continuously. In efforts to adapt the S-layer for display of foreign peptides and proteins, we noted a proteolytic activity that affected S-layer monomers with foreign inserts. The cleavage was precise, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…One solution to this problem could be rapid degradation of protein that cannot be exported. We have suggested that the S-layer-associated protease (the product of sapA), which appears poised to recognize defects in the nascent RsaA monomer, might play such a role (47). The data here, however, gave no indication that detectable degradation occurs.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…One solution to this problem could be rapid degradation of protein that cannot be exported. We have suggested that the S-layer-associated protease (the product of sapA), which appears poised to recognize defects in the nascent RsaA monomer, might play such a role (47). The data here, however, gave no indication that detectable degradation occurs.…”
Section: Discussioncontrasting
confidence: 49%
“…On this latter point, a preliminary threading of the RsaF a and RsaF b proteins onto the homologous TolC protein (for which the structure has been determined) predicted exposed chargedense regions in the interior of the transporter channel (data not shown). We estimate that this may be the reason why the addition of the furin cleavage site (RKKR) leads to a blockage of RsaA transport, while a variety of other recombinant RsaA proteins with 100 to 200 amino acid insertions have been readily secreted (34,47).…”
Section: Discussionmentioning
confidence: 99%
“…5, compare lanes 1 and 4 or lanes 2 and 5). In JS4015, the Sap deficiency derives from a point mutation in the active site (38), which reduces its activity but may not abolish it completely and so may allow for some residual cleavage of RsaA(1-277). This may account for the presence of a small amount of the cleaved version of RsaA(1-277) when JS4015 cells were used as target cells for RsaA(1-277) reattachment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with anchoring domains for S-layer proteins of grampositive bacteria, which are usually three repeats of the ϳ55-amino-acid SLH domain (4). Although the native function of Sap is unknown, our previous model of Sap-mediated editing of the recombinant S-layer suggested that because the C terminus of Sap is homologous with the N terminus of RsaA, Sap associates with nascent, but still internal, RsaA monomers and cleaves some mutant versions of RsaA (38). A recombinant S-layer protein subjected to Sap proteolysis would result in the separation of the RsaA C-terminal secretion signal from the rest of RsaA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation